2011
DOI: 10.5507/bp.2011.042
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Fatty Acid Binding Protein and C-Reactive Protein Levels as Indicators of Insulin Resistance Development

Abstract: Background. Adipocyte fatty acid-binding protein (aFABP) has recently been identified as a potential circulating marker for metabolic syndrome. C-reactive protein (CRP), a sensitive marker of inflammation, is increased in individuals with diabetes and metabolic syndrome due to the development of subclinical inflammation. The study uses logistic regression models to analyze the relations between aFABP and CRP along with other parameters of insulin resistance. The objective was to investigate the potential use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(22 reference statements)
0
1
0
1
Order By: Relevance
“…In addition, A-FABP might have proinflammatory properties related to lipopolysaccharide-induced inflammation by forming a positive feedback loop with the JNK/c-Jun signaling cascade 53 , which is involved in impaired insulin action. Several studies showed correlation between A-FABP and proinflammatory factors, like C-reactive protein (CRP), and their similar importance in predicting insulin resistance 54,55 .…”
Section: Adipocyte Fatty Acid Binding Protein (A-fabp)mentioning
confidence: 99%
“…In addition, A-FABP might have proinflammatory properties related to lipopolysaccharide-induced inflammation by forming a positive feedback loop with the JNK/c-Jun signaling cascade 53 , which is involved in impaired insulin action. Several studies showed correlation between A-FABP and proinflammatory factors, like C-reactive protein (CRP), and their similar importance in predicting insulin resistance 54,55 .…”
Section: Adipocyte Fatty Acid Binding Protein (A-fabp)mentioning
confidence: 99%
“…Istraživanje je pokazalo da su osobe sa razvijenim MS imale znatno veće vrednosti koncentracije CRP i da su kod njih znatno učestalije merene koncentracije CRP veće od 5 mg/L u odnosu na osobe koje nisu razvile MS, što ukazuje na postojanje hronične, sistemske, zapaljenjske reakcije niskog intenziteta kod njih, i ovaj nalaz je u saglasnosti s nalazima drugih studija (3,7,(9)(10)(11)(12). Izmerene prosečne koncentracije CRP od 2,46 mg/L kod ispitanika kontrolne grupe i 5,33 mg/L kod ispitanika sa MS jasno pokazuju proinflamatornu reakciju i uticaj MS i njegovih karakteristika na porast koncentracije CRP, najviše kao posledicu gojaznosti i značajno većih vrednosti antropometrijskih parametara, obima struka i BMI.…”
Section: Diskusijaunclassified